AMPLIFIED RIBOSOMAL DNA RESTRICTION ANALYSIS (ARDRA) BAKTERI DENGAN POTENSI ANTIMIKROB YANG BERASOSIASI DENGAN SPONS Jaspis sp. - Hermawaty Abubakar (Jurnal Natural, 2010)
Sponges are one of the components that compose coral reef which have a potential bioactive substance that has not been utilized. Sponges are generally able to survive in marine waters were nutrients are poor because of associations with other organisms, especially bacteria. This study aimed to isolate and characterize bacteria (endosymbiont and ectosimbion) that produce antimicrobial compounds, and analyze genetic diversity based on Amplified Ribosomal DNA Restriction Analysis (ARDRA). The results of isolation obtained 138 bacterial isolates, which are 70 endofit isolates and 68 surfaces isolates respectively. The results obtained, based on antimicrobial test, was 32 bacterial isolates (45.71%) of the total bacterial isolates that have endofit antimicrobial activity, whereas on the surface bacteria, 20 bacterial isolates (29.41%) of the total surface of the bacterial isolates also have antimicrobial activity. Genetic diversity was carried out on 30 isolates that has the best antimicrobial activity. Amplyfication of 16S rRNA gene is done using specific primers, 63f and 1387r. The profile of 16S rRNA gene band shows a high diversity, which is generated after cutting with three restriction enzymes i.e. RsaI, HaeIII and HinfI. The three restriction enzymes have different cuts and properties. Construction of phylogenetic trees based on analysis of Amplified Ribosomal DNA restriction, grouped 30 isolates from the sponge Jaspis sp. which have a microbial activity on seven filotipe. This grouping is based on the similarities cuts of sites of each isolate after restriction by three different restriction enzymes.